Uneven outcomes from private infrastructure finance: evidence from two case studies. Issue 7 (3rd October 2021) - Bayliss, Kate; Romero, Maria Jose; Waeyenberge, Elisa Van
ABSTRACT: The Sustainable Development Goals have intensified calls for private finance to address a so-called financing gap. This paper provides a critical assessment of the promotion of private finance in infrastructure, assessing two public–private partnerships (PPPs), celebrated for their success in mobilising private funds: a road in Senegal and a hospital in Brazil. While these projects may have had some positive outcomes, their apparent success relies on extensive support from governments and donors. Our findings question the efficacy of private financing as a response to shortages of infrastructure funds. Rather than plugging the financing gap, private finance risks creating fiscal burdens.